A Novel of PSO Modified Carrier-Based PWM Technique to Reduce Total Harmonic Distortion in The Inverter Topology 7-level Cascade H-Bridge Triple Voltage Boosting Gain - Falah, Moh Zainul; Sujito, Sujito; Aripriharta, Aripriharta (Universitas Ahmad Dahlan, 2024)
This research focuses on optimizing the Particle Swarm Optimization (PSO) method in switching modulation to reduce total harmonic distortion (THD) in a 7-level Cascade H-Bridge Multi-Level Inverter (MLI) topology with triple voltage boosting gain. MLI Cascade H-Bridge is an inverter topology that is widely used in power conversion applications because of its ability to produce high voltage output with low harmonics. However, the resulting THD is still a major challenge in improving power quality. In this research, the PSO method is applied to find optimal parameters in switching modulation that can minimize THD. The research results show that the PSO method succeeded in reducing THD significantly with a THD value of 7.80% whereas the previous THD was 17.27%. The implementation of PSO in switching modulation is expected to be an effective solution for inverter applications in industry and power systems. The THD value from the PSO optimization is stated to be in accordance with IEEE 519 standards with a maximum permitted THD of 8%. This value is better than previous research, namely 17.27%.